Efektivitas Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Berbantuan Media Wordwall Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Nur Fathir, Jihani; Puadi, Evan Farhan Wahyu (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the effectiveness of the Numbered Head Together (NHT) cooperative learning model assisted by Wordwall media on students' mathematical problem-solving abilities. The research method used is a quasi-experiment with a Non-equivalent Pretest-Posttest Control Group Design. The research sample consists of 60 students from class XI MAN 1 Kuningan, selected through purposive sampling, with 30 students in the experimental group and 30 students in the control group. The research instruments include tests and questionnaires. Data analysis was conducted using independent sample t-tests and Mann-Whitney U tests. The research results show that there are differences in students' mathematical problem-solving abilities. There is a significant difference in the improvement of mathematical problem-solving abilities between the experimental class and the control class. Students responded positively to NHT learning assisted by Wordwall. These findings indicate that the implementation of the cooperative learning model NHT assisted by Wordwall media is effective in improving students' mathematical problem-solving abilities